Incarcerated Small Bowel Herniation in a Stoma Mimicking Sigmoid End Colostomy Prolapse - Kaoru Abe; Daisuke Yamai; Chihiro Katsumi; Manabu Oyamatsu; Kenji Sato (Case Reports in Gastroenterology, 2024)
Introduction: A stoma prolapse is easy to diagnose by visual examination, and it rarely incarcerates. Therefore, manual reduction is usually performed as soon as the diagnosis is made. In this report, we describe a case of stoma prolapse that could not be reduced manually and ruptured because an incarcerated parastomal hernia occurred in the stoma, mimicking stoma prolapse. Case Presentation: A 66-year-old woman underwent total hysterectomy, bilateral salpingo-oophorectomy, pelvic and para-aortic lymphadenectomy, omentectomy, resection of dissemination, and low anterior resection with formation of a sigmoid end colostomy for endometrial cancer with infiltration of the rectum. Fourteen months after the initial operation, she presented with stoma prolapse and multiple episodes of vomiting. The prolapsed stoma was 20 cm in length, appeared swollen and edematous, and was somewhat firm. Although it looked viable, some of the mucosa was darkish red, indicating congestion. Therefore, the diagnosis was sigmoid end colostomy prolapse with an ischemic component. An attempt at manual reduction resulted in rupture, so an emergency laparotomy was performed. Intraoperatively, we found that the ileum was incarcerated in the aperture created where the colostomy had been formed. When the incarcerated ileum was released, the stoma prolapse could be reduced easily. The end colostomy was refashioned in the left upper quadrant of the abdomen. Conclusion: An incarcerated parastomal hernia can mimic stoma prolapse. If the findings differ from those of typical stoma prolapse, imaging should be performed to confirm whether another clinical entity is involved in the stoma prolapse.